2022
DOI: 10.1136/bmjsem-2021-001253
|View full text |Cite
|
Sign up to set email alerts
|

Maximal aerobic capacity is associated with lifting capacity, but not with self-reported functioning measures in patients with primary chronic low back pain: a cross-sectional study

Abstract: ObjectiveMaximal exercise testing is considered the gold standard to assess V̇O2max. However, maximal exercise testing was previously deemed unfeasible and unsafe in chronic low back pain (CLBP) patients. Consequently, most previous studies on aerobic capacity and functioning in patients with CLBP were performed with submaximal testing protocols. A recent study demonstrated the safety, feasibility and tolerance of maximal exercise testing in patients with CLBP. Therefore, the relation between aerobic capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In our study, we found a significant correlation between the 2MST and the sport domain of BQ, these findings may indicate that sport is recommended to maintain good levels of cardiorespiratory fitness in people with chronic low back pain. Patients with chronic low back pain are vulnerable populations, as they have lower levels of strength [ 33 ], aerobic capacity [ 34 ], VO2max [ 35 ], and metabolic thresholds, negatively impacting the walking economy, quality of life, and practice of physical exercise [ 6 ]. The 2MST is a strategy to assess these patients without exposing them to the maximum physical exertion tests, respecting their biological individuality as well as their disability.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found a significant correlation between the 2MST and the sport domain of BQ, these findings may indicate that sport is recommended to maintain good levels of cardiorespiratory fitness in people with chronic low back pain. Patients with chronic low back pain are vulnerable populations, as they have lower levels of strength [ 33 ], aerobic capacity [ 34 ], VO2max [ 35 ], and metabolic thresholds, negatively impacting the walking economy, quality of life, and practice of physical exercise [ 6 ]. The 2MST is a strategy to assess these patients without exposing them to the maximum physical exertion tests, respecting their biological individuality as well as their disability.…”
Section: Discussionmentioning
confidence: 99%